Evaluation of the Restoration Success of Endodontic Therapy of the Primary Molars - Kirzioglu, Zuhal; Gungor, Ozge Erken; Ciftci, Z Zahit (European Journal of Dentistry, 2011)
Objectives: The aim of this study was to evaluate the clinical and radiographic success rates of pulpotomized primary molar teeth restored with a compomer material with using United States Public Health Service (USPHS) criteria. Methods: In 173 primary molars of 156 child patients, aged within 4-9 years (mean age: 6.1±1.4 years), conventional pulpotomy treatment were performed. The teeth treated using calcium hydroxide, formocresol or ferric sulphate. After pulpotomy procedure, teeth were restored with compomer material. The teeth were evaluated as clinically and radiographically during a period of 12-24 months. Both of success of pulpotomy treatment and also restorative material (compomer material) were evaluated during follow-up period. The data were assessed with chi-square test. Results: At the end of the first year, 45% of initial treated teeth were checked, but only 18% were checked at the end of the second year. The first year success rates in the groups treated with CH, FC, and FS were 87.5%, 95%, and 79%, respectively, and, as the number of controllable patients was lower, the success rates on available teeth were determined to be 88.3% and 80%, respectively, according to the materials at the end of the second year. Restorations having been made, they were analyzed in accordance with USPHS criteria. Conclusions: At the end of the first year, 67.5% of compomer restorations were detected to be original and healthy and at the end of the second year, 57% were deemed healthy. No statistically significant relationships were found between marginal adaptation, secondary caries and pulpotomy success (chi-square test, P>.05). Among the three groups, there is no significant difference in terms of success. The least successful age group was defined as 4-6 years. (Eur J Dent 2011;5:415-422)
Keywords: Primary molar; Endodontic therapy; Success rate; Pulpotomy